Televizyona karşı anababa aracılığı: Kısıtlayıcı aracılığın biçimleri - Melike Türkan BAĞLI (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In order to cope with the negative effects of television, parents may restrict the use of television by their children. This kind of mediation is called “restrictive mediation” in the literature. In this study, in order to figure out the forms and “why”s of restrictive mediation, four families with preschool age children were visited in their homes and observed in the natural flow of their daily lives by the researcher. After the visits were completed, the researcher conducted interviews with parents on the details of their attitudes and regulations on television viewing and other aspects of their family life. The results indicated that the parents used direct and indirect ways to restrict their children’s television viewing. Forming and stating rules about viewing and restricting while explaining the reasons for restriction were among the direct restrictive mediations. It was seen that restricting without allowing children to know that they are restricted was carried out as a way of indirect restrictive mediation. The other indirect restrictive mediation ways were (a) offering alternative programs, channels or activities substituting the actual program or channel viewed, (b) implying that the reasons of the rules were different than the real ones, (c) pretending that source of the rules was not the parents themselves. Spatial restrictiveness (by regulating physical characteristics of their homes) and manipulating third persons (by telling what to do to other persons than the parent who tried to restrict) seemed the efforts to create an appropriate atmosphere for restriction. The reasons for restriction were the television content covering violence, sex and bad language